A visit to the hospital - Hautzig, Deborah (New York : Random House, 1985)
Grover visits the hospital to find out what to expect when he goes to have his tonsils out.
Keywords: Hospitals -- Fiction; Medical care -- Fiction; Tonsillectomy -- Fiction; Puppets -- Fiction